Measuring safety management practices relationship with safety performance among Police officers - Mani Raj, Muniandy (2020)
Safety management practices is a key in minimizing workplace hazardous accidents by improving workplace safety conditions, as well as enabling employers and employees to change their attitudes and behaviors to make safety and health a priority. The purpose of this study is to measure the level of safety performance particularly safety compliance and safety participation among the police officers and to measure the relationship between safety compliance and safety performance as dependent variable with independent variables of safety management practices which are safety training, safety rules and procedure, management commitment, communication and feedback, safety promotion and policies and employee participation. The research method is quantitative analysis and adopting a crosssectional approach in data gathering. Primary data generated form the questionnaire chooses as a data collection. Random sampling method was used in collecting the data and the population is from the police officers in Johor. Quantitative analysis using SPSS version 25.0 was used and the result is shown that the validity and reliability of six factors of safety management practices that may affect the safety performance (safety compliance and safety participation). The findings in this study will provide a good insight for future researchers and practitioners in the field to identify problems and solutions that contribute to the safety and health at the workplace.